Incompatibility of the circadian protein BMAL1 and HNF4α in hepatocellular carcinoma. Issue 1 (December 2018) - Fekry, Baharan; Ribas-Latre, Aleix; Baumgartner, Corrine; Deans, Jonathan; Kwok, Christopher; Patel, Pooja; Fu, Loning; Berdeaux, Rebecca; Sun, Kai; Kolonin, Mikhail; Wang, Sidney; Yoo, Seung-Hee; et al.
Abstract Hepatocyte nuclear factor 4 alpha (HNF4α) is a master regulator of liver-specific gene expression with potent tumor suppressor activity, yet many liver tumors express HNF4α. This study reveals that P1-HNF4α, the predominant isoform expressed in the adult liver, inhibits expression of tumor promoting genes in a circadian manner. In contrast, an additional isoform of HNF4α, driven by an alternative promoter (P2-HNF4α), is induced in HNF4α-positive human hepatocellular carcinoma (HCC). P2-HNF4α represses the circadian clock geneARNTL (BMAL1), which is robustly expressed in healthy hepatocytes, and causes nuclear to cytoplasmic re-localization of P1-HNF4α. We reveal mechanisms underlying the incompatibility of BMAL1 and P2-HNF4α in HCC, and demonstrate that forced expression of BMAL1 in HNF4α-positive HCC prevents the growth of tumors in vivo. These data suggest that manipulation of the circadian clock in HNF4α-positive HCC could be a tractable strategy to inhibit tumor growth and progression in the liver. Hepatocyte nuclear factor 4 alpha (HNF4α) is regulated by different promoters to generate two isoforms, one of which functions as a tumor suppressor. Here, the authors reveal that induction of the alternative isoform in hepatocellular carcinoma inhibits the circadian clock by repressing BMAL1, and the reintroduction of BMAL1 prevents HCC tumor growth.